Spatial equalization of selected sound source by digital inverse filtering - Ciesielka, Wojciech (Archives of Acoustics, 2007)
The article presents digital inverse equalizers, enabling active sound control by means ofdirectional characteristics equalization of selected sound source. Theoretical grounds of thesesystems are based on inverse filtration theory. Mathematical model of the equalizer, as well asexperimental results confirming effectiveness of its operation have also been described in thestudy, which presents directional characteristics of Visaton BG17 loudspeaker, and its selectedimpulse responses prior to, and after equalization.